Complement Activation Is a Prominent Feature of MOGAD. Issue 6 (9th October 2021) - Keller, Christian W.; Lopez, Joseph A.; Wendel, Eva‐Maria; Ramanathan, Sudarshini; Gross, Catharina C.; Klotz, Luisa; Reindl, Markus; Dale, Russell C.; Wiendl, Heinz; Rostásy, Kevin; Brilot, Fabienne; Lünemann, Jan D.
Abstract : Myelin oligodendrocyte glycoprotein (MOG)‐antibody (Ab)–associated diseases (MOGADs) account for a substantial proportion of pediatric and adult patients who present with acquired demyelinating disorders. Its pathogenesis and optimal therapy are incompletely understood. We profiled systemic complement activation in adult and pediatric patients with MOGAD compared with patients with relapse‐onset multiple sclerosis, patients with neuromyelitis optica spectrum disorder, and pediatric control and adult healthy donors. Proteins indicative of systemic classical and alternative complement activation were substantially increased in patients with MOGAD compared to control groups. Elevated levels were detected in both adult and pediatric cases and across all clinical syndromes. Complement inhibition should be explored for its therapeutic merit in patients with MOGAD. ANN NEUROL 2021;90:976–982